2014
DOI: 10.1093/nar/gku971
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing endogenous type I CRISPR-Cas systems for programmable gene repression

Abstract: CRISPR-Cas systems have shown tremendous promise as heterologous tools for genome editing and transcriptional regulation. Because these RNA-directed immune systems are found in most prokaryotes, an opportunity exists to harness the endogenous systems as convenient tools in these organisms. Here, we report that the Type I-E CRISPR-Cas system in Escherichia coli can be co-opted for programmable transcriptional repression. We found that deletion of the signature cas3 gene converted this immune system into a progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
227
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(246 citation statements)
references
References 59 publications
6
227
0
1
Order By: Relevance
“…Studies have revealed that among Cas proteins in Type I CRISPR-Cas systems, Cas3 has as a key role in programing gene expression [30] by acting as a single-strand DNA nuclease and ATP-dependent helicase [31]. Csy1-4 proteins constitute the cascade [32], wherein Csy4 func-tions in processing crRNA transcripts, whereas Csy1-3 proteins are required to stabilize the crRNA produced by Csy4 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that among Cas proteins in Type I CRISPR-Cas systems, Cas3 has as a key role in programing gene expression [30] by acting as a single-strand DNA nuclease and ATP-dependent helicase [31]. Csy1-4 proteins constitute the cascade [32], wherein Csy4 func-tions in processing crRNA transcripts, whereas Csy1-3 proteins are required to stabilize the crRNA produced by Csy4 [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the emergence of sgRNA design rules is promising to accelerate the development of CRISPRi even more [29]. Recent work is also showing that other CRISPR/Cas systems can be engineered, such as the endogenous type I-E system of E. coli [30 ], to create a diverse range of CRIPSR/Cas-based regulators, each with unique design principles and advantages.…”
Section: Repurposed Crispr Systems -The Best Of Rnas and Proteinsmentioning
confidence: 99%
“…Exploitation of endogenous and orthogonal systems CRISPR-Cas systems are found in approximately 46% of bacteria and 84% of Archaea [43], highlighting the potential for genome editing applications using endogenously active systems [44]. However, there is a general paucity of systems with characterized PAMs and confirmed activity in interference [45].…”
Section: Dna Repair Mechanisms In Bacteriamentioning
confidence: 99%